Drivers of seasonal to decadal mixed layer carbon cycle variability in subantarctic water in the Munida Time Series - Vance, Jesse M.; Currie, Kim; Suanda, Sutara H.; Law, Cliff S. (Frontiers in Marine Science, 2024)
Using ancillary datasets and interpolation schemes, 20+ years of the Munida Time Series (MTS) observations were used to evaluate the seasonal to decadal variability in the regional carbon cycle off the southeast coast of New Zealand. The contributions of gas exchange, surface freshwater flux, physical transport processes and biological productivity to mixed layer carbon were diagnostically assessed using a mass-balanced surface ocean model. The seasonal and interannual variability in this region is dominated by horizontal advection of water with higher dissolved inorganic carbon (DIC) concentration primarily transported by the Southland Current, a unique feature in this western boundary current system. The large advection term is primarily balanced by net community production and calcium carbonate production, maintaining a net sink for atmospheric CO2 with a mean flux of 0.84±0.62 mol C m-2 y-1. However, surface layer pCO2 shows significant decadal variability, with the growth rate of 0.53±0.26 μatm yr-1 during 1998–2010 increasing to 2.24±0.47 μatm yr-1 during 2010–2019, driven by changes in advection and heat content. Changes in circulation have resulted in the regional sink for anthropogenic CO2 being 50% higher and pH 0.011±.003 higher than if there had been no long-term changes in circulation. Detrended cross-correlation analysis was used to evaluate correlations between the Southern Annular Mode, the Southern Oscillation Index and various regional DIC properties and physical oceanographic processes over frequencies corresponding the duration of the MTS. The drivers of variability in the regional carbon cycle and acidification rate indicate sensitivity of the region to climate change and associated impacts on the Southern Ocean and South Pacific.